2022
DOI: 10.3389/fnagi.2022.927315
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Traditional Chinese Exercise in Improving Gait and Balance in Cases of Parkinson's Disease: A Systematic Review and Meta-analysis

Abstract: BackgroundThe efficacy of traditional Chinese exercise (TCE)-based intervention in the improvement of motor function in patients with Parkinson's disease (PD) is controversial. The present study aimed to assess the effects of TCE on balance and gait outcomes, as well as motor symptoms in individuals with PD, and evaluate potential discrete moderators such as TCE dosage-related variables.MethodPubMed, Embase, Cochrane's Library, Web of Science, Medline, and Scopus were systematically searched from their dates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Previous studies have also reported on the limited effectiveness of strength training, dance, and aerobic exercise in improving walking speed (Karpodini et al, 2022; Radder et al, 2020). However, some reviews have found that Tai Chi and BGT can significantly improve walking speed (Radder et al, 2020; Wu et al, 2022). This difference may be due to the limited number of studies included in this study, in which only studies with sham-treated controls were included and studies with controls receiving other active physiotherapy were excluded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have also reported on the limited effectiveness of strength training, dance, and aerobic exercise in improving walking speed (Karpodini et al, 2022; Radder et al, 2020). However, some reviews have found that Tai Chi and BGT can significantly improve walking speed (Radder et al, 2020; Wu et al, 2022). This difference may be due to the limited number of studies included in this study, in which only studies with sham-treated controls were included and studies with controls receiving other active physiotherapy were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be due to the limited number of studies included in this study, in which only studies with sham-treated controls were included and studies with controls receiving other active physiotherapy were excluded. Walking endurance, as measured by the 6-MWT, is a more commonly used indicator than walking speed (Karpodini et al, 2022; Radder et al, 2020; Wu et al, 2022). Both mind-body exercise and aerobic exercise have been found to improve aerobic endurance (Winser et al, 2018; Zhen et al, 2022), so it is no surprise that both were found to significantly improve walking endurance in people with PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As light to moderate exercises, TCEs are safe, effective and economical. They combine balance and coordination capacity on the basis of aerobic exercise and emphasise the physical–psychological connection 38. Because of this, these traditional sports are very popular among people of all ages in China and have become quite popular around the world in recent years 39.…”
Section: Discussionmentioning
confidence: 99%
“…They combine balance and coordination capacity on the basis of aerobic exercise and emphasise the physical-psychological connection. 38 Because of this, these traditional sports are very popular among people of all ages in China and have become quite popular around the world in recent years. 39 Evidence has demonstrated the effectiveness of TCEs in improving cardiopulmonary and musculoskeletal system function and quality of life in older adults.…”
Section: Open Accessmentioning
confidence: 99%